2009
DOI: 10.1186/cc7876
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells-1 expression on monocytes is associated with inflammation but not with infection in acute pancreatitis

Abstract: Introduction Acute pancreatitis (AP) is usually a mild and selflimiting disease, but some patients develop a severe form that is associated with high mortality. In AP, local inflammation is followed first by the systemic inflammatory response syndrome and then by the compensatory anti-inflammatory response syndrome, which is defined by low human leukocyte antigen (HLA)-DR expression on monocytes, increased concentration of the anti-inflammatory cytokine IL-10, and decreased monocyte function. Our aim was to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
(39 reference statements)
2
32
0
5
Order By: Relevance
“…[10][11][12] Serum sTREM-1 was found to be higher in patients with AP than in healthy volunteers. [13] Thus, it is important to investigate the role of TREM-1 in the development of SAP associated with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Serum sTREM-1 was found to be higher in patients with AP than in healthy volunteers. [13] Thus, it is important to investigate the role of TREM-1 in the development of SAP associated with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes are a major source of TREM-1 in inflammation (Arts et al, 2011;Cavaillon, 2009;Ferat-Osorio et al, 2009;Wong-Baeza et al, 2006) and their expression has been shown to be regulated in several bacterial and fungal infections, including infections of the respiratory track, gut or amniotic fluid (Aoki et al, 2004;Begum et al, 2004;Buckland et al, 2011;del Fresno et al, 2008;How et al, 2011;Kusanovic et al, 2011;Richeldi et al, 2004;Schmausser et al, 2008). Individual microbial components, such as lipopolysaccharide (LPS) and peptidoglycan, can cause up-regulation of cell surface-localized TREM-1 by monocytes, as well as release in its soluble (s)TREM-1 form (Begum et al, 2004;Gibot et al, 2004b;Gomez-Pina et al, 2007;Murakami et al, 2007;Ramanathan et al, 2005;Zeng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality of severe AP remains very high: 25 to 50%. 55,56 In patients with AP, plasma sTREM-1 concentrations were higher in non-survivors than in survivors, 55 and may be helpful to early predict the development of organ dysfunction. 57 Expression of TREM-1 on myeloid cells in these patients is upregulated and correlates to disease severity.…”
Section: Effects Of the Trem-1 Pathway Modulation During Inflammatorymentioning
confidence: 99%